2018
DOI: 10.1080/17429145.2018.1432772
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress revealed physiological, biochemical and gene-expressional variations in ‘Yoshihime’ peach (Prunus Persica L) cultivar

Abstract: It is indispensable to comprehend the mechanism that regulates plant responses to drought conditions to intensify the water use efficiency of stone fruits. The physiological, biochemical and molecular responses of drought-treated peach leaves were investigated. Results revealed that drought-treated plants manifested a significant attenuation in water potential as compared to control plants. Furthermore, sorbitol and proline contents were accumulated contrary to glucose, fructose, and sucrose that were dwindled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 60 publications
7
44
1
Order By: Relevance
“…It affects the production of both rain-fed and irrigated crops. As plants are sessile in nature, they respond to drought stress in a series of processes at physiological, biochemical and molecular level, allowing them to escape or adapt to unfavorable conditions [4,5]. Furthermore, drought impairs nutrient uptake and transport, inhibits photosynthesis, loss of cell turgidity and accumulation of reactive oxygen species, crop growth and productivity and in extreme cases crop failure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It affects the production of both rain-fed and irrigated crops. As plants are sessile in nature, they respond to drought stress in a series of processes at physiological, biochemical and molecular level, allowing them to escape or adapt to unfavorable conditions [4,5]. Furthermore, drought impairs nutrient uptake and transport, inhibits photosynthesis, loss of cell turgidity and accumulation of reactive oxygen species, crop growth and productivity and in extreme cases crop failure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the chlorophyll a fluorescence parameters and photosynthetic pigment levels of selected cultivars (Bio-902, CS-14, Pusa-Tarak and Laxmi) may be due to the intrinsic differences between the cultivars. It can be assumed from our results that the reduction in photosynthetic performance of all the cultivars is due to the damage of photosynthetic machinery (PSI and PSII) (Mittal et al 2012) or due to deviation of biochemical processes involving in PSII reaction centers or due to decline in the catalytic activity of Rubisco or due to inhibition of chlorophyll synthesis as it is a key component of photosynthesis in plants (Batra et al 2014;Haider et al 2018). The elevation in temperature also results in reduced maximal quantum yield (PSII) of plants (Hasanuzzaman et al 2013) such as tomato (Morales et al 2003), Populus (Ferreira et al 2006) and rice (Han et al 2009;Vani et al 2001).…”
Section: Discussionmentioning
confidence: 89%
“…However, APX has higher scavenging affinity for H 2 O 2 in comparison to CAT (Chalanika de silva and Asaeda 2017). A significant increase is observed in the activities of ROS enzymes (SOD, POD, CAT, GPX and APX) with respect to abiotic stress (Haider et al 2018;Vardharajulaet al 2011). In this study, each cultivar of Brassica juncea also showed a continuous rise in antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Souza et al (2015), the ideal range for total N content in peach seedlings is from 509.94 to 617.24 (mg plant -1 ), which agrees with the present research. Perennial fruit species of the genus Prunus, such as the peach tree [Prunus persica L. (Basthc)], accumulate N in the form of free proteins or amino acids, as well as non-structural carbohydrates that include starch and soluble sugars (sucrose, glucose, fructose and sorbitol) (Haider et al, 2018). Such molecules play an essential role in vegetative growth, providing structural components for the formation of new cells and consequently maximum biomass production.…”
Section: Resultsmentioning
confidence: 99%